Effects of hydrogen-rich water on the nutrient composition and antioxidative characteristics of sprouted black barley. (30th November 2019) - Guan, Qi; Ding, Xin-Wen; Jiang, Rui; Ouyang, Peng-Ling; Gui, Juan; Feng, Lei; Yang, Li; Song, Li-Hua
Highlights: The hydrogen-rich water (HRW) was used in the processing of sprouted black barley. The effects of HRW on germination speed of black barley were evaluated. The bioactive components in HRW-treated black barleys were identified using UPLC-MS. HRW treatment could increase the growth speed of black barleys at 10–15 °C. The levels of partial functional components increased in HRW-treated black barleys. Abstract: Hydrogen gas (H2 ), a multifunctional signaling molecule, has received increasing attention in recent years. In the present study, hydrogen-rich water (HRW) (2 ppm) was used for the processing of sprouted black barley ( Hordeum distichum L.), and the results showed that the HRW treatment could significantly increase the germination rate and growth rate of black barley (P < 0.05). A chemical component analysis showed that in sprouted black barley, the HRW treatment could change the distribution of phytochemicals (e.g., the ionic strength of guanosine), increase the concentrations of free vanillic acid, coumaric acid, sinapic acid, conjugated sinapic acid, Ca and Fe and the hydroxyl radical scavenging rate, and decrease the protein, fat, starch and dietary fibre contents compared with the results obtained after treatment with ultra-pure water (P < 0.05). HRW can be used for the processing of sprouted grains to effectively increase their germination efficiency and concentrations of bioactive phytochemicals.